The Use of Flashcards in Vocabulary Mastery of The Students With Down Syndrom at SLB Negeri Pagaralam - Umi Kalsum; Fadilaturrahmah Fadilaturrahmah; Ido Yupiter (JEIT (Journal of Educational Innovations and Technologies), 2025)
It will be more complex and challenging when the English knowledge have to be delivered to the down syndrome students who essentially have serious interference in understanding concepts and ideas. Nevertheless, the teachers surely expect that students with down syndrome are able to comprehend English as students commonly. The main focus of this research was to find out there was any significant improvement in vocabulary mastery after applying flashcards to the students with down syndrom at SLB Negeri Pagaralam?” Pre-experimental design one group of pre test and post test method was used in this research. The result of pre-test and post-test in class were compared by using paired sample t-test. The value of t-obtained was 10.156, at the significance value p<0.05 in two tailed testing with df = 4, the critical value of the t-table was 2.776. Since the value of t-obtained was higher than the critical value of t-table, It mean there was any significant improvement in vocabulary mastery after applying flashcards. So that flashcards media could improve students’ vocabulary mastery to the students with down syndrom at SLB Negeri Pagaralam.